2019
DOI: 10.1111/ecc.12987
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity and responsiveness of the Mandarin (Simplified) Chinese version of the EORTC QLQ-OH45 among cancer patients

Abstract: Purpose The goal of our study was to evaluate the reliability, validity, responsiveness and acceptability of the Mandarin (simplified) Chinese version of the EORTC QLQ‐OH45. Methods From October 2017 to February 2018, 393 cancer patients were enrolled from three different hospitals in China. A forward and backward translation was made to develop the Mandarin (simplified) Chinese version of EORTC QLQ‐OH15. The QLQ‐C30 and QLQ‐OH15 questionnaires (which we have assembled and named QLQ‐OH45 in this paper) were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, discriminant validity was examined by the correlation coefficient between each item and other domains. A higher correlation for each item with its own domain than that with other domains were indicators of satisfied convergent validity and discriminant validity [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, discriminant validity was examined by the correlation coefficient between each item and other domains. A higher correlation for each item with its own domain than that with other domains were indicators of satisfied convergent validity and discriminant validity [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…QoL of patients was also assessed at M0, M3, M6, and M12 after initiation of study intervention, using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (QLQ-C30 Scale). 13,14 The QLQ-C30 included 30 items, covering five functional domains (physical, role, cognitive, emotional, and social), three symptom domains (fatigue, pain, and nausea and vomiting), a global health domain, and six single domains. The first 28 items of the questionnaire used a 4-point Likert-type response scale ranging from 1 (not at all) to 4 (very much).…”
Section: Qol Assessmentmentioning
confidence: 99%
“…As was to be expected, the coefficients of temporal stability were much smaller than those obtained in studies with time intervals of only a few days between measurement points. In the nine studies featuring time intervals between 1 day and 2 weeks in lengths 5 13 the stability coefficients of the 2-item global health/QoL scale were between 0.82 and 0.93, with the exception of one study that examined brain tumor patients. The averaged Pearson correlation our study found ( r = 0.45) for measurement periods between 3 and 12 months long means that only 20% ( r 2 = 0.202) of the variance of the t2 measurement can be explained by the t1 scores.…”
Section: Discussionmentioning
confidence: 97%
“…However, knowledge about the temporal stability of QoL scores over time periods longer than one month is very limited. Test–retest reliability is considered a quality criterion of questionnaires, and there are multiple studies on test–retest reliability that used time intervals of 1–2 days 5 8 , 3–4 days 9 , 10 or 1–2 weeks 11 13 . While these coefficients are relevant for assessing the reliability of the instruments, clinicians are also interested in the question of how well a QoL questionnaire score can predict a patients’ QoL several months later.…”
Section: Introductionmentioning
confidence: 99%